Trophic diversity of chemosymbiont hosts in deep-sea hydrothermal vents using amino acid nitrogen isotopes - Suh, Yeon Jee; Ju, Se-Jong; Kim, Min-Seob; Choi, Hyuntae; Shin, Kyung-Hoon (Frontiers in Marine Science, 2023)
Chemosymbiotic species inhabiting deep-sea hydrothermal vents are known to rely on microbial symbionts for nutrition. However, the relative contributions of heterotrophic energy sources to their diets remain poorly understood. In this study, we investigate the trophic positions (TP) of symbiontbearing taxa, including vent mussels, snails, and shrimps, and examine the contribution of copepods and detrital organic matter (OM) to the food chain. Amino acid nitrogen isotopic compositions (δ 15 NAA) were used to investigate the TP of vent mussels (Bathymodiolus septemdierum and Gigantidas vrijenhoeki), snails (Alviniconcha spp.), and shrimps (Alvinocaris sp. and Rimicaris kairei) from two different vent environments. δ 15 NAA values in copepods and OM were also measured. Microbial resynthesis index (ΣV) was calculated to predict the contribution of reworked OM as an energy source to the hydrothermal vent ecosystem. Variations in TP were observed among vent mussels and snails from different vent environments, with higher TP in species from diffusing vents than in those from black smoker vents. Shrimps dwelling in a single diffusing vent exhibited distinct TP, suggesting that microhabitat and phylogeny may influence their energy acquisition. Notably, copepods occupied higher TPs than expected, possibly owing to the consumption of detrital OM. Our findings provide new insights into the trophic diversity of chemosymbiotic species in deepsea hydrothermal vents and demonstrate the utility of δ 15 NAA analysis as a tool for unraveling food web dynamics and ecosystem functioning in these unique environments.